Errors in Determining the Thermophysical Characteristics of Heterogeneous High-Energy Materials by the Laser-Pulse Method; Journal of Engineering Physics and Thermophysics; Vol. 88, iss. 6 - Kats M. D. Mark Davydovich (2015, 2015)
Title screen